Prototype of 3D printed mecanum wheel - Mateja, Krzysztof (Technical Sciences, 2023)
This article presents the results of work related to design, analysis and selection of the 3D printed mecanum wheels. Initial CAD model does not include material type of the rollers. Rollers were printed in 4 types of filament: PLA, ABS, PETG, FLEX. Analysis, tests and target destination of use allowed to choose the best material for rollers which will meet the usage requirements. Next step after choose material for roller were assembly of the wheels. Wheels were tested on the simple platform. Assembled 4 wheels (two left and two right) allowed to carry out tests to verify the mobility of the mobile robot and check the adhesion between rollers and ground.